Parasite Contamination of Sand and Soil from Daycare Sandboxes and Play Areas - Theresa W Gyorkos; Evelyne Kokoskin-Nelson; J Dick MacLean; Julio C Soto (Canadian Journal of Infectious Diseases)
Objectives: To determine if there was parasite contamination in the sand and soil in daycare sandboxes and play areas, with the goal of developing practice guidelines for their management.